2018
DOI: 10.7554/elife.35373
|View full text |Cite
|
Sign up to set email alerts
|

Release and spread of Wingless is required to pattern the proximo-distal axis of Drosophila renal tubules

Abstract: Wingless/Wnts are signalling molecules, traditionally considered to pattern tissues as long-range morphogens. However, more recently the spread of Wingless was shown to be dispensable in diverse developmental contexts in Drosophila and vertebrates. Here we demonstrate that release and spread of Wingless is required to pattern the proximo-distal (P-D) axis of Drosophila Malpighian tubules. Wingless signalling, emanating from the midgut, directly activates odd skipped expression several cells distant in the prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 92 publications
3
32
1
Order By: Relevance
“…Although Wg has been characterised as a diffusible ligand, acting on a range of several cells, it was reported that the substitution of the wg locus by a membrane tethered version of Wg (NRT-Wg) gives rise to flies that develop apparently normally (although poorly viable), with no overt morphological phenotypes, suggesting that a long range action by diffusion of Wg may not be required during development (Piddini and Vincent, 2009). However, some studies using the NRT-Wg Drosophila line have shown that Wg signalling at a distance is required in specific contexts (Beaven and Denholm, 2018). Here we show that short-range diffusion of Wg is indeed required for the appropriate patterning of the wing margin, as initially reported.…”
Section: Discussionsupporting
confidence: 83%
“…Although Wg has been characterised as a diffusible ligand, acting on a range of several cells, it was reported that the substitution of the wg locus by a membrane tethered version of Wg (NRT-Wg) gives rise to flies that develop apparently normally (although poorly viable), with no overt morphological phenotypes, suggesting that a long range action by diffusion of Wg may not be required during development (Piddini and Vincent, 2009). However, some studies using the NRT-Wg Drosophila line have shown that Wg signalling at a distance is required in specific contexts (Beaven and Denholm, 2018). Here we show that short-range diffusion of Wg is indeed required for the appropriate patterning of the wing margin, as initially reported.…”
Section: Discussionsupporting
confidence: 83%
“…The need for secreted Wg has been recently challenged, with Wg tethering to the membrane (NRT-wg) showing Wg secretion to be largely dispensable for development (Alexandre et al, 2014). In contrast, other recent studies suggest that Wg release and spreading is necessary (Beaven and Denholm, 2018;Pani and Goldstein, 2018;Stewart et al, 2019). We find tethering Wg at the NMJ synapse increases extracellular Wg ligand levels, with no change in mature bouton numbers.…”
Section: Discussionmentioning
confidence: 56%
“…Development of the MTs occurs during embryogenesis and they are completely functional by the first instar larval stage. The development and physiology of the fly renal tubule have been extensively investigated and reviewed in previous publications (Beyenbach et al, 2010;Denholm, 2013;Skaer, 1996;Dow, 2012;Beaven and Denholm, 2018;Bunt et al, 2010). Each tubule is composed of different segments (ureter, main, initial and transitional segments) that are functionally and genetically distinct (Chintapalli et al, 2012), and has two main epithelial cell types: the principal cell (PC) and the stellate cell (SC) (Dow, 2012;Denholm et al, 2003).…”
Section: Introductionmentioning
confidence: 99%